BMP2 immune complexes promote new bone formation by facilitating the direct contact between osteoclasts and osteoblasts. (August 2021) - Xu, Yamei; Yang, Yao; Hua, Ziyi; Li, Shuang; Yang, Zhenyu; Liu, Qianzi; Fu, Gang; Ji, Ping; Wu, Qingqing
Abstract: BMP2 antibody is proposed as a promising replacement for rhBMP2 in bone tissue engineering. Although studies have demonstrated its osteoinductive efficacy, the underlying osteogenic mechanism and adverse reactions of specific BMP2 antibody are not clarified yet, making it difficult to optimize the antibody for future application. By establishing BMP2 immune complexes (BMP2-ICs) ex vivo, we were able to introduce BMP2-ICs directly in vivo and found that BMP2-ICs promoted bone formation while suppressing osteoclastogenesis. However, ex vivo osteoclastogenic assays showed that BMP2-ICs promoted osteoclastogenesis by binding FcγR and activating PLCγ2 phosphorylation. Given that BMP2-ICs react with osteoblast and osteoclast lineage cells by the conjugated BMP2 domain and the Fc domain respectively, we introduced BMP2-ICs into coculture system of the two lineage cells and found that BMP2-ICs promoted osteogenesis while suppressing osteoclastogenesis by facilitating osteoblast-osteoclast contact and activating the EphrinB2-EphB4 signaling. This bidirectional function of BMP2-ICs was reproduced in the cranial bone resorption model, where osteoblast and osteoclast lineage cells co-localized. This study excluded the hidden problem of osteoclast overactivation that usually comes with rhBMP2 and clarified the first evidence of the mechanism of antibody-mediated bone regeneration, suggesting BMP2-ICs may present a promising therapy for bone diseases related with disrupted osteoclast-osteoblast interaction. Graphical abstract: Image 1